First Clinical Experience of 68Ga-FAPI PET/CT in Tertiary Cancer Center: Identifying Pearls and Pitfalls - Akram Al-Ibraheem; Ahmed Saad Abdlkadir; Ula Al-Rasheed; Dhuha Al-Adhami; Feras Istatieh; Farah Anwar; Marwah Abdulrahman; Rula Amarin; Issa Mohamad; Asem Mansour (Diagnostics)
Background/Objectives: Over the past four years, 68Ga-fibroblast activation protein inhibitor (FAPI) positron emission tomography/computed tomography (PET/CT) has been established at a tertiary cancer care facility in Jordan. This retrospective study aims to explore tracer uptake metrics across various epithelial neoplasms, identify diagnostic pitfalls associated with 68Ga-FAPI PET/CT, and evaluate the influence of 68Ga-FAPI PET/CT staging results on changes in therapeutic intent compared to gold standard molecular imaging modalities. Methods: A total of 48 patients with biopsy-confirmed solid tumors underwent 77 68Ga-FAPI PET/CT examinations for molecular imaging assessment, encompassing neoplasms originating from the gastrointestinal tract, head and neck, hepatobiliary system, pancreas, breast, and lung. Results: Notably, pancreaticobiliary tumors exhibited the highest tracer uptake, with mean maximum standardized uptake values (SUVmax) and tumor-to-background ratios (TBR) surpassing 10. A comparative sub-analysis of 68Ga-FAPI PET metrics in 20 treatment-naïve patients revealed a significant correlation between 68Ga-FAPI uptake metrics and tumor grade (Spearman’s rho 0.83; p = 0.00001). Importantly, the results from 68Ga-FAPI PET/CT influenced treatment decisions in 35.5% of the cases, primarily resulting in an escalation of management plans. A total of 220 diagnostic challenges were identified across 88.3% of the scans, predominantly within the musculoskeletal system, attributed to degenerative changes (99 observations). Conclusions: This comprehensive analysis highlights the potential significance of 68Ga-FAPI PET/CT in oncological imaging and treatment strategy, while also emphasizing the necessity for meticulous interpretation to mitigate diagnostic challenges.